Investigação de potenciais biomarcadores em saliva de pacientes diagnosticados com Doença de Wilson - Ferro, Julia Lima Ribeiro (Universidade Federal de São Carlos, 2023)
INVESTIGATION OF POTENTIAL BIOMARKERS IN SALIVA FROM PATIENTS DIAGNOSED WITH WILSON DISEASE. Wilson disease (WD) is a rare inherited disorder characterized by excessive intracellular copper in the liver, brain, and other vital organs. Copper overload in the body can lead to a series of complications, including neurological problems, acute or chronic liver failure, kidney problems, and psychiatric manifestations. WD is a progressive disease and, if left untreated, results in serious and potentially life-threatening disabilities. Therefore, early diagnosis is essential for effective treatment and preventing severe clinical manifestations. The present work evaluated differentiating metabolites in saliva samples from individuals with WD compared to healthy individuals. For this, a global metabolomics approach was performed using liquid chromatography coupled with high-resolution mass spectrometry (LC-HRMS), allowing the annotation of potential candidates for biomarkers, and obtaining information about changes in the metabolic pathways of the individual’s group. Saliva samples from individuals with WD (n=24) and healthy individuals (n=39) were analyzed, and the results showed 39 metabolites that differed significantly between the two groups (p ≤ 0,05; VIP ≥ 1), with 15 of them being putatively annotated. Among these metabolites, sedoheptulose-7-phosphate, palmitic acid, N-undecanoylglycine, suberic acid, and pyrocatechol have been previously reported and are associated with Alzheimer disease, schizophrenia, Parkinson disease, cancer, and kidney disease. The metabolites N-methyl-salsolinol, sphinganine, and betaine have already been described as potential biomarkers for Parkinson and Wilson diseases. In the present study, an upregulation of betaine was observed in individuals with WD. Moreover, the metabolite ceramide Cer(d18:2/20:4) was detected as the most significant metabolite in differentiating the two groups by the ROC curve. While Cer(d18:2/20:4) is a new metabolite in the context of WD, high levels of ceramides have been linked to neurodegenerative diseases, diabetes, and cardiovascular diseases. Therefore, it is also considered an important metabolite for future studies related to WD, which can aid in faster and more accurate diagnosis of rare syndromes. Additionally, non-invasive saliva sampling is desirable as an affordable and convenient biofluid monitoring alternative.
Investigation of potential biomarkers in saliva from patients diagnosed with Wilson Disease
Keywords: Doença de Wilson; LC-HRMS; Doença hereditária rara; Metabolômica; Saliva; Wilson disease; Metabolomics; Rare inherited disorder; CIENCIAS BIOLOGICAS; CIENCIAS EXATAS E DA TERRA::QUIMICA